Here among the Mangroves - Martinez, Krissie Zamora (The Bookmark, 2015)
"From blue crabs busy during daytime to flying squirrels active at night, get to know the unique animals that call the Philippine mangrove swamps their home. Young readers will delight in the catchy counting rhyme, beautifully-detailed illustrations, and fun facts about each creature!"